Dietary and Nutritional Strategy for the Prevention and Management of Hyperuricemia - A. Priyadharshini; Manali Sudhir; Anirudh Manikandan; Ahalya S.P (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The global prevalence of gout which occurs due to increased serum urate levels owing to changing diet and lifestyle is ever increasing and not much is known about the efficacy and impact of modifiable dietary factors.Methods: Databases such as PubMed, ScienceDirect, Google scholar were searched extensively using appropriate keywords which matched the scope of the study.Results and Conclusion: While the etiology of gout is multi-factorial, modification of dietary factors contributes to the lowering of urate levels in blood. Studies shown that Vitamin C, coffee, tea, cherries, turmeric and many other supplements which may have a significant role in the management of gout along with pharmacological treatment, hence studies are suggested to conduct on dietary intervention for the prevention and management of hyperuricemia.